Language expressions in constructing physical masculinity in Indonesian teen lit - Zahro, Azizatuz; Santoso, Anang; Dawud, Dawud (citeus, 2020)
Teen lit serves a central position in the conception of masculinity in teenagers due to its closeness to them as readers. For teenagers, physical masculinity is relatively highlighted compared to masculinity in other dimensions. Physical masculinity is expressed through classic names, which is related to strength, and is signified by ‘provincial’ names. Physical masculinity is also conveyed through the expressions of the eyes and figures. Besides, a specific cultural icon typically related to handsomeness is also used to construct physical masculinity in teen lit.